PROSEDUR BERACARA DI MAHKAMAH KONSTITUSI DALAM PENYELESAIAN UJI MATERIL TERHADAP PERATURAN PERUNDANG-UNDANGAN - Yoksa Adrinata; Nur Rahmah (Jurnal GeoCivic, 2025)
The Constitutional Court of the Republic of Indonesia holds a strategic role within the state system, particularly in upholding the integrity and supremacy of the 1945 Constitution of the Republic of Indonesia. One of its principal authorities is the judicial review of laws against the Constitution, aimed at annulling legal norms that contradict the 1945 Constitution and ensuring the protection of citizens’ constitutional rights. This article seeks to provide an in-depth explanation of the procedural mechanisms for judicial review cases at the Constitutional Court and to assess the extent to which these procedures are effective in safeguarding constitutional protection. The study employs a normative juridical approach with descriptive and interpretative analysis of legislation and Constitutional Court decisions. The findings indicate that although the procedural framework has been systematically regulated, its implementation still faces challenges, particularly concerning public access to constitutional justice and the effectiveness of decision enforcement.